Recent successes in therapeutics for Ebola virus disease: no time for complacency. Issue 9 (September 2020) - Iversen, Patrick L; Kane, Christopher D; Zeng, Xiankun; Panchal, Rekha G; Warren, Travis K; Radoshitzky, Sheli R; Kuhn, Jens H; Mudhasani, Rajini R; Cooper, Christopher L; Shurtleff, Amy C; Nasar, Farooq; Sunay, Melek ME; et al.
Summary: The PALM trial in the Democratic Republic of the Congo identified a statistically significant survival benefit for two monoclonal antibody-based therapeutics in the treatment of acute Ebola virus disease; however, substantial gaps remain in improving the outcomes of acute Ebola virus disease and for the survivors. Ongoing efforts are needed to develop more effective strategies, particularly for individuals with severe disease, for prevention and treatment of viral persistence in immune-privileged sites, for optimisation of post-exposure prophylaxis, and to increase therapeutic breadth. As antibody-based approaches are identified and advanced, promising small-molecule antivirals currently in clinical stage development should continue to be evaluated for filovirus diseases, with consideration of their added value in combination approaches with bundled supportive care, their penetration in tissues of interest, the absence of interaction with glycoprotein-based vaccines, and filoviral breadth.